Compositional strategies for timbral blend in mixed electroacoustic music and portfolio of original compositions - Collins, M (2023)
In this thesis, I examine the role that timbre may play in the oft-perceived aesthetic disconnect between the acoustic and electronic forces in mixed electroacoustic music by establishing an analytical framework with which to carry out timbral analyses on a set of mixed electroacoustic works: ‘Salt Canyons’ from The Inner Universe (1983) by Priscilla McLean; RAS (2000, rev. 2011) by Natasha Barrett; and Scirocco (1983) by Maggi Payne. This framework develops on Walther-Hansen’s theory of sound as a combination of the ‘sound-in-itself’ and the sound’s apparent source, Wallmark and Kendall’s application of conceptual metaphor theory to timbre semantics, and Walther-Hansen’s model of metaphorical descriptions for recorded sound. Within this framework, I conceptualise timbre phenomenologically as an ever-shifting combination of its source and its contents, and systematise the use of culturally situated intersubjective metaphor to describe said contents. I also introduce two concepts for the purposes of the analyses: a timbral thread, which contains any sound or set of sounds over time that could be reasonably perceptually categorised as being produced by one source; and timbral blend, which I define as the capacity of sounds from two or more physical sources to coalesce so that a listener is not likely to determine that there is an aesthetic disconnect between them. I also establish a means for graphically representing these timbral threads using a flowchart-type method. Using this framework, I analyse the works by describing and graphically representing the timbral threads that can be delineated within them, and thus establish shared common compositional strategies used to achieve timbral blend between the acoustic and electronic forces across the set of works. Each analysis is also contextualised by a review of any relevant compositional preferences from the composers concerned, so that any influence these may have had on the compositional strategies used for timbral blend can be determined.